Prediction of net energy of feeds for broiler chickens - Aye-Cho Tay-Zar; Manoosak Wongphatcharachai; Pairat Srichana; Pierre-André Geraert; Jean Noblet (Animal Nutrition, 2024)
Net energy (NE) enables the prediction of more accurate feed energy values by taking into account the heat increment which is approximately 25% of apparent metabolizable energy (AME) in poultry. Nevertheless, application of NE in poultry industry has not been practiced widely. To predict the NE values of broiler diets, 23 diets were prepared by using 13 major ingredients (wheat, corn, paddy rice, broken rice, cassava pellets, full-fat soybean, soybean meal, canola meal, animal protein, rice bran, wheat bran, palm kernel meal and palm kernel oil). The diets were formulated in order to meet the birds' requirements and get a wide range of chemical compositions (on DM basis; 33.6% to 55.3% for starch; 20.8% to 28.4% for CP, 2.7% to 10.6% for ether extract [EE] and 7.0% to 17.2% for NDF), with low correlations between these nutrients and low correlations between the inclusion levels of ingredients allowing for the calculation of robust prediction equations of energy values of diets or ingredients. These diets were fed to Ross 308 broilers raised in 12 open-circuit respiratory chambers from 18 to 23 d of age (4 birds per cage) and growth performance, diet AME content and heat production were measured, and dietary NE values were calculated. The trial was conducted on a weekly basis with 12 diets measured each week (1 per chamber), 1 of the 23 diets (reference diet) being measured each week. Each diet was tested at least 8 times. In total, 235 energy balance data values were available for the final calculations. Growth performance, AME (15.3 MJ/kg DM on average) and AME/GE (79.4% on average) values were as expected. The NE/AME value averaged 76.6% and was negatively influenced by CP and NDF and positively by EE in connection with efficiencies of AME provided by CP, EE and starch for NE of 73%, 87% and 81%, respectively. The best prediction equation was: NE = (0.815 × AME) – (0.026 × CP) + (0.020 × EE) – (0.024 × NDF) with NE and AME as MJ/kg DM, and CP, EE and NDF as % of DM. The NE prediction equations from this study agree with other recently reported equations in poultry and are suitable for both ingredients and complete feeds.